2023
DOI: 10.21511/pmf.11(1).2022.10
|View full text |Cite
|
Sign up to set email alerts
|

The impact of governance quality on central bank’s independence

Abstract: The stable functioning of the public finance system requires a rational regulatory apparatus. The central bank occupies a special place in this system. Science and practice prove that the central bank’s political and economic independence determines its effectiveness. Thus, it is crucial to determine the prerequisites for ensuring its independence. The study aims to assess the influence of governance quality on the central bank’s independence, considering the variance of the socio-political development of coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Scientists emphasize the need for reforms in the independence of central banks to maintain their regulatory effectiveness, reduce risks and stabilize the financial sector (Habiba, 2023). It has been empirically confirmed that the level of independence of central banks is closely related to the quality of the general system of public administration in the country (Vasylieva et al, 2022). Financial crises demonstrate the existing shortcomings in the system of banking regulation and form the basis for the search for their improvement.…”
Section: Literature Reviewmentioning
confidence: 93%
See 1 more Smart Citation
“…Scientists emphasize the need for reforms in the independence of central banks to maintain their regulatory effectiveness, reduce risks and stabilize the financial sector (Habiba, 2023). It has been empirically confirmed that the level of independence of central banks is closely related to the quality of the general system of public administration in the country (Vasylieva et al, 2022). Financial crises demonstrate the existing shortcomings in the system of banking regulation and form the basis for the search for their improvement.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Researchers have con-firmed that the reason for the inefficient banking system is the unbalanced distribution of resources, which leads to a loss of stability (Rizk, 2022). Internal and external imbalances are the reason for applying a tighter restrictive monetary policy (Vasilyeva et al, 2013). So, for example, the recapitalization policy of central banks has a positive effect on competition in the banking system (Yuni & Attama, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Political power attempts to achieve short-term economic growth through an expansionist monetary policy that created inflation to sway public opinion and win elections (Beju, 2008;Ouyang et al, 2022). Many empirical studies have found that average inflation is negatively related to CBI measures (Cukierman et al, 1992;Eijffinger & de Haan, 1996;Walsh, 2003;Vasylieva et al, 2022;Khokhych et al, 2023;Kerimov et al, 2023aKerimov et al, , 2023b; studies have shown that countries with higher levels of CBI tend to have lower inflation rates and are more successful in controlling inflation. The relationship between CBI and monetary stability has been a subject of extensive empirical analysis in the literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though international integration contributes to the unification of regulatory mechanisms of different countries (Babenko et al, 2017), the specifics of their application are determined by the conditions of national development. In particular, inflationary trends depend on the specifics of a country's economic development in each specific period (Aliyeva, 2022;Vasilyeva et al, 2013). In particular, in periods of war, the monetary policy of central banks has significant differences from the traditional approach to regulation (Danylyshyn & Bohdan, 2022), and in periods of financial crises, it is significantly softened (Oliveira & Santos, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%